Disposisi Religio-Strategis Skemata Algoritma Mark C. Taylor dan Yuval Noah Harari - Simanjuntak, Mardohar B. B. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2018)
Religion has probably been very influencial since the dawn of civilization. The next imperative question would be how something that has always been in the very discourse of human achievement stays in the centre stage for generations to come. To tackle this question, it is important to see what religion actually is related to its ability to manifest the self. The question can even be extended further by examining how the self – central to epistemological inquiries – be justified by the presence of consciousness. Constructing answers to this colossal undertaking of religious identity invites a thorough understanding of how human beings can be taken as conscious. The subsequent agenda is to determine whether consciousness lies within or – on the other way around – outside; whether it is naturally personal or else impersonal. Having dealt with these risky arguments allows us to slightly probe something in the future concerning the debatable fate of being a religious self. Both Mark C. Taylor’ rejuvenated schemata and Yuval Noah Harari’ reinvented algorhytms have provided an extra breathing space that facilitates broader chances for religion to further play a farther role in an even broader horizon of foreseeable possibilities.